A wear-resistant pipeline powder and preparation method thereof

By using modified epoxy resin and molybdenum disulfide/cubic sulfide nanohybrid materials in the pipeline powder, the problem of poor wear resistance in low temperature environments is solved, and excellent wear resistance at low temperatures is achieved.

CN118530646BActive Publication Date: 2025-05-02NINGBO BOSHIDUN NANO NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410678844.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-05-02
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

Epoxy resin-type pipeline powder has poor wear resistance in low temperature environments, resulting in limited application in pipeline engineering.

Method used

Wear-resistant pipeline powder including polyurethane powder, modified epoxy resin powder, curing agent, nano-wear-resistant particles and additives are used to improve the toughness and wear resistance of the coating by combining adipic acid-based epoxy resin in the modified epoxy resin and molybdenum disulfide/cubic sulfide nanohybrid materials.

Benefits of technology

In low temperature environments, the pipe powder coating exhibits extremely excellent wear resistance, reducing wear and cracks, and improving the service life of the pipe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004865030040000081
    Figure BDA0004865030040000081
Patent Text Reader

Abstract

The present application relates to the technical field of powder coatings, and more specifically, it relates to a wear-resistant pipeline powder and a preparation method thereof. A wear-resistant pipeline powder comprises the following raw materials in parts by weight: 20-30 parts of polyurethane powder, 40-50 parts of modified epoxy resin powder, 8-14 parts of curing agent, 15-25 parts of nano wear-resistant particles and 4-6 parts of auxiliary agent; the modified epoxy resin comprises adipic acid-based epoxy resin and bisphenol A-type epoxy resin, the curing agent is obtained by mixing diethylenetriamine and polyamide curing agent 650, and the wear-resistant particles are molybdenum disulfide / copper sulfide nano hybrid materials. The coating obtained by curing the pipeline powder of the present application has excellent low-temperature wear resistance and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of powder coatings, and more specifically, to a wear-resistant pipeline powder and a preparation method thereof. Background Art

[0002] Pipeline powder refers to a powder coating used in pipeline engineering. It is usually composed of resin materials, pigments, fillers and other additives. Its purpose is to protect or decorate pipelines. Powder coatings can usually be applied to the surface of pipelines through electrostatic spraying or electrophoretic coating, and then fixed by baking to form a solid coating, thereby improving the corrosion resistance and weather resistance of pipelines.

[0003] Epoxy resin has the advantages of high strength, good chemical stability, creep resistance and strong adhesion, so it is widely used in resin materials in pipeline powder. However, after curing, epoxy resin presents a three-dimensional network structure with high crosslinking density and large internal stress, which leads to its brittleness and poor wear resistance. At present, the improvement of epoxy resin wear resistance is carried out by filling nanoparticles, but in low temperature environment, the molecular velocity inside the epoxy coating decreases, resulting in low temperature embrittlement effect, which makes the wear resistance of epoxy coating still relatively poor, thus limiting its use in pipeline powder. Summary of the invention

[0004] In order to improve the defect of poor wear resistance of epoxy resin type pipeline powder in low temperature environment, the present application provides a wear-resistant pipeline powder and a preparation method thereof.

[0005] In a first aspect, the present application provides a wear-resistant pipeline powder, which adopts the following technical solution:

[0006] A wear-resistant pipeline powder comprises the following raw materials in parts by weight: 20-30 parts of polyurethane powder, 40-50 parts of modified epoxy resin powder, 8-14 parts of curing agent, 15-25 parts of nano wear-resistant particles and 4-6 parts of auxiliary agent;

[0007] The modified epoxy resin includes adipic acid-based epoxy resin and bisphenol A-type epoxy resin, the curing agent is obtained by mixing diethylenetriamine and polyamide curing agent 650, and the wear-resistant particles are molybdenum disulfide / copper sulfide nano-hybrid materials.

[0008] The wear mechanism of epoxy resin is that epoxy resin is very brittle, and microcracks can easily expand under external forces, leading to local cracking. The addition of molybdenum disulfide can significantly narrow the wear marks, and greatly improve the delamination and peeling phenomena. The reason is that molybdenum disulfide has a layered structure, and its layers are connected by weak van der Waals forces, which makes it easy for the layers to slide relative to each other during friction, which helps to form a transfer film, thereby improving the wear resistance of the epoxy resin coating.

[0009] Copper sulfide is a hard particle that can improve the bearing capacity of the epoxy coating and play a pinning role on the network structure of the epoxy coating, thereby effectively dispersing the stress concentration caused by the friction process, inhibiting the further expansion of cracks, and thereby improving the wear resistance of the epoxy resin coating.

[0010] Compared with adding molybdenum disulfide or copper sulfide alone, adding molybdenum disulfide / copper sulfide nanohybrid materials can simultaneously obtain the transfer film function of molybdenum disulfide and the bearing capacity function of copper sulfide, thereby achieving a synergistic promotion effect and further improving the wear resistance of the epoxy resin coating.

[0011] The mechanism of low-temperature embrittlement of epoxy coatings is that the internal molecular velocity of epoxy coatings decreases at low temperatures, thus showing a brittle characteristic. Adipic acid-based epoxy resins contain flexible chains, which improve the toughness of the entire pipeline powder system. At the same time, adipic acid-based epoxy resins also increase the freedom of macromolecular chains in the three-dimensional network of the entire pipeline powder, thereby accelerating the movement between molecules and causing a certain degree of deformation when the pipeline powder system is impacted, thereby absorbing the impact energy and inhibiting the further expansion of cracks, thereby improving the wear resistance of the epoxy resin coating.

[0012] In summary, when the pipeline powder contains both adipic acid-based epoxy resin and molybdenum disulfide / copper sulfide nano-hybrid material, the pipeline powder can also have extremely excellent wear resistance at low temperatures.

[0013] Preferably, the mass ratio of the adipic acid-based epoxy resin to the bisphenol A-based epoxy resin is (1-2):10; the mass ratio of the diethylenetriamine to the polyamide curing agent 650 is (1-2):2.

[0014] When the adipic acid-based epoxy resin and the bisphenol A epoxy resin are in the above mass ratio, and the diethylenetriamine and the polyamide curing agent 650 are in the above mass ratio, the prepared pipeline powder will have better low-temperature wear resistance after curing.

[0015] Preferably, the adipic acid-based epoxy resin comprises the following raw materials: 0.05-0.15 mol of adipic acid, 1.0-1.4 mol of epichlorohydrin, 0.5-1.5 mmol of benzyltriethylammonium chloride and 6-10 g of sodium hydroxide.

[0016] Preferably, the preparation method of the adipic acid-based epoxy resin is: first, adipic acid, epichlorohydrin and benzyltriethylammonium chloride are mixed, then reacted in a 95°C water bath for 2 hours, then sodium hydroxide is added in portions, 1 g each time, with an interval of 15 minutes, and then reacted for 3-4 hours, and finally filtered while hot, and rotary evaporated at 125°C to obtain the adipic acid-based epoxy resin.

[0017] Preferably, the modified epoxy resin comprises the following raw materials in parts by mass: 100 parts of bisphenol A epoxy resin, 10-20 parts of adipic acid-based epoxy resin, 10-14 parts of hydroxypropyl quaternary ammonium salt, 14-20 parts of toluene-3,5-diisocyanate, 20-30 parts of N,N-dimethylformamide and 1-3 parts of dibutyltin dilaurate.

[0018] In a humid climate and moderate temperature environment, the surface of the pipeline powder coating is prone to the growth of harmful microorganisms such as bacteria and mold, which can cause the coating to discolor, powder, and fall off, further deteriorating the wear resistance of the pipeline powder coating.

[0019] Hydroxypropyl quaternary ammonium salts can destroy the cell membrane of microorganisms, interfere with the charge balance and metabolic process inside microbial cells, cause the denaturation and inactivation of microbial proteins, and cause the loss of microbial nucleic acids. Therefore, quaternary ammonium salts are a kind of high-quality antibacterial material. However, hydroxypropyl quaternary ammonium salts are highly soluble in water. Therefore, in rainy weather, hydroxypropyl quaternary ammonium salts are easily precipitated, which in turn affects the antibacterial properties of pipeline powder coatings.

[0020] During the curing process of the adipic acid-based epoxy resin, the epoxy group will open the ring to form a hydroxyl group. Since the curing process is in a heated state, under the catalysis of dibutyltin dilaurate, the two isocyanate groups of toluene-3,5-diisocyanate will react with the hydroxyl group formed after the opening of the adipic acid-based epoxy resin and the hydroxyl group on the hydroxypropyl quaternary ammonium salt, respectively, thereby fixing the hydroxypropylene quaternary ammonium salt to the long chain of the pipeline powder system, effectively reducing the possibility of precipitation or deviation of the hydroxypropyl quaternary ammonium salt, and further improving the antibacterial properties of the hydroxypropylene quaternary ammonium salt.

[0021] Preferably, the molybdenum disulfide / copper sulfide nano-hybrid material comprises the following raw materials: 0.2-0.3 g of copper nitrate trihydrate, 0.05-0.15 g of hexadecyltrimethylammonium bromide, 0.7-0.9 g of thiourea and 0.3-0.5 g of ammonium molybdate tetrahydrate.

[0022] Preferably, the preparation method of the molybdenum disulfide / copper sulfide nano-hybrid material comprises the following steps:

[0023] S1. Add 0.25 g of copper nitrate trihydrate to 80 ml of deionized water and stir until completely dissolved, then add 0.1 g of hexadecyltrimethylammonium bromide and continue stirring until dissolved, then add 0.15 g of thiourea and continue stirring for 1 h, finally transfer to a 100 ml polytetrafluoroethylene reactor, react at 150 ° C for 12 h, and finally filter, wash and dry to obtain copper sulfide powder;

[0024] S2, 0.18g of ammonium molybdate tetrahydrate and 0.3g of thiourea were added to 30ml of deionized water and mixed and stirred for 1.5h, then transferred to a 50ml polytetrafluoroethylene reactor, reacted at 210°C for 24h, and finally filtered, washed and dried to obtain molybdenum disulfide powder;

[0025] S3, add 0.18g of ammonium molybdate tetrahydrate and 0.3g of thiourea to 80ml of deionized water, mix and stir for 1.5h, then add 0.05g of copper sulfide powder of S1, continue stirring for 2h and ultrasonicate for 30min, then transfer to a 100ml polytetrafluoroethylene reactor, react at 210°C for 24h, finally filter, wash and dry to obtain molybdenum disulfide / copper sulfide nanohybrid material.

[0026] In a second aspect, the present application provides a method for preparing wear-resistant pipeline powder, using the following technical solution:

[0027] A method for preparing wear-resistant pipeline powder, comprising the following steps:

[0028] The polyurethane powder and modified epoxy resin powder are mixed, and then the curing agent, nano wear-resistant particles and additives are added in turn. The mixture is stirred at a stirring speed of 800-1000r / min for 10 minutes, and finally melt-extruded by a twin-screw, with a melting section temperature of 180-200℃ and a die extrusion temperature of 200-210℃. Finally, the tablets are air-cooled, ground and sieved, the products are inspected, and the finished products are packaged and stored to obtain wear-resistant pipe powder.

[0029] In summary, this application has the following beneficial effects:

[0030] 1. Compared with adding molybdenum disulfide or copper sulfide alone, adding molybdenum disulfide / copper sulfide nanohybrid materials can simultaneously obtain the transfer film function of molybdenum disulfide and the bearing capacity function of copper sulfide, thereby achieving a synergistic promotion effect and further improving the wear resistance of the epoxy resin coating.

[0031] 2. Adipic acid-based epoxy resin contains flexible chains, which improves the toughness of the entire pipeline powder system. At the same time, adipic acid-based epoxy resin also increases the freedom of the macromolecular chain in the three-dimensional network of the entire pipeline powder, thereby accelerating the movement between molecules. When the pipeline powder system is impacted, it undergoes a certain degree of deformation, thereby absorbing the impact energy and inhibiting the further expansion of the cracks. Combined with the wear resistance improvement mechanism of molybdenum disulfide / copper sulfide nano-hybrid materials, the pipeline powder can also have extremely excellent wear resistance at low temperatures.

[0032] 3. During the curing process of the adipic acid-based epoxy resin, the epoxy group will open the ring to form a hydroxyl group. Since the curing process is in a heated state, under the catalysis of dibutyltin dilaurate, the two isocyanate groups of toluene-3,5-diisocyanate will react with the hydroxyl group formed after the opening of the adipic acid-based epoxy resin and the hydroxyl group on the hydroxypropyl quaternary ammonium salt, respectively, thereby fixing the hydroxypropylene quaternary ammonium salt to the long chain of the pipeline powder system, effectively reducing the possibility of precipitation or deviation of the hydroxypropyl quaternary ammonium salt, and further improving the antibacterial properties of the hydroxypropylene quaternary ammonium salt. DETAILED DESCRIPTION

[0033] The present application is further described in detail below in conjunction with Examples 1-9 and Comparative Examples 1-3.

[0034] raw material

[0035] Polyurethane powder Hualixing Plastics; Diethylenetriamine CAS: 111-40-0; Polyamide curing agent 650; Bisphenol A epoxy resin Nantong Xingchen; Adipic acid CAS: 124-04-9; Epichlorohydrin CAS: 106-89-8; Benzyltriethylammonium chloride CAS: 56-37-1; Zinc stearate CAS: 557-05-1; Sodium hydroxide CAS: 1310-73-2; Hydroxypropyl quaternary ammonium salt CAS: 1369 20-10-0; Toluene-3,5-diisocyanate CAS: 26471-62-5; N,N-dimethylformamide CAS: 68-12-2; Dibutyltin dilaurate CAS: 77-58-7; Copper nitrate trihydrate CAS: 10031-43-3; Hexadecyltrimethylammonium bromide CAS: 57-09-0; Thiourea CAS: 62-56-6; Ammonium molybdate tetrahydrate CAS: 12054-85-2.

[0036] Example

[0037] Example 1

[0038] A wear-resistant pipeline powder comprises the following raw materials: 25g of polyurethane powder, 45g of modified epoxy resin powder, 11g of curing agent, 20g of nano wear-resistant particles and 5g of auxiliary agent-zinc stearate.

[0039] The curing agent is a mixture of diethylenetriamine and polyamide curing agent 650, and the mass ratio of diethylenetriamine to polyamide curing agent 650 is 3:4. The nano wear-resistant particles are molybdenum disulfide / copper sulfide nano hybrid materials, and the molybdenum disulfide / copper sulfide nano hybrid materials include the following raw materials: 0.25g of copper nitrate trihydrate, 0.1g of hexadecyltrimethylammonium bromide, 0.75g of thiourea and 0.36g of ammonium molybdate tetrahydrate.

[0040] The preparation method of molybdenum disulfide / copper sulfide nano-hybrid material comprises the following steps:

[0041] S1. Add 0.25 g of copper nitrate trihydrate to 80 ml of deionized water and stir until completely dissolved, then add 0.1 g of hexadecyltrimethylammonium bromide and continue stirring until dissolved, then add 0.15 g of thiourea and continue stirring for 1 h, finally transfer to a 100 ml polytetrafluoroethylene reactor, react at 150 ° C for 12 h, and finally filter, wash and dry to obtain copper sulfide powder;

[0042] S2, 0.18g of ammonium molybdate tetrahydrate and 0.3g of thiourea were added to 30ml of deionized water and mixed and stirred for 1.5h, then transferred to a 50ml polytetrafluoroethylene reactor, reacted at 210°C for 24h, and finally filtered, washed and dried to obtain molybdenum disulfide powder;

[0043] S3, add 0.18g of ammonium molybdate tetrahydrate and 0.3g of thiourea to 80ml of deionized water, mix and stir for 1.5h, then add 0.05g of copper sulfide powder of S1, continue stirring for 2h and ultrasonicate for 30min, then transfer to a 100ml polytetrafluoroethylene reactor, react at 210°C for 24h, finally filter, wash and dry to obtain molybdenum disulfide / copper sulfide nanohybrid material.

[0044] The modified epoxy resin powder is obtained by mixing the following raw materials: 100g of bisphenol A epoxy resin, 15g of adipic acid-based epoxy resin, 12g of hydroxypropyl quaternary ammonium salt, 17g of toluene-3,5-diisocyanate, 25g of N,N-dimethylformamide and 2g of dibutyltin dilaurate.

[0045] The adipic acid-based epoxy resin includes the following raw materials: 0.1 mol adipic acid, 1.2 mol epichlorohydrin, 1.0 mmol benzyltriethylammonium chloride and 8 g sodium hydroxide;

[0046] The preparation method of adipic acid-based epoxy resin is as follows: first, adipic acid, epichlorohydrin and benzyltriethylammonium chloride are mixed, then reacted in a 95°C water bath for 2 hours, then sodium hydroxide is added in portions, 1 g each time, with an interval of 15 minutes, and then reacted for 4 hours, finally filtered while hot, and subjected to rotary evaporation at 125°C to obtain adipic acid-based epoxy resin.

[0047] The preparation method of wear-resistant pipe powder is as follows: polyurethane powder and modified epoxy resin powder are mixed, and then curing agent, nano wear-resistant particles and additives are added in sequence, mixed and stirred at a stirring speed of 1000r / min for 10 minutes, and finally melt-extruded by a twin-screw, the melting section temperature is 190°C, the head extrusion temperature is 200°C, and finally the tablets are air-cooled, ground and sieved, the products are inspected, and the finished products are packaged and stored to obtain wear-resistant pipe powder.

[0048] Example 2-3

[0049] The difference from Example 1 is that the added amounts of the components of the wear-resistant pipe powder are different, as shown in Table 1.

[0050] Table 1 Addition amount of each component of wear-resistant pipeline powder of Examples 1-3 / g

[0051] Example 1 Example 2 Example 3 Polyurethane powder 25 20 30 Modified epoxy resin powder 45 40 50 Curing agent 11 8 14 Nano wear-resistant particles 20 25 15 Additives 5 4 6

[0052] Embodiment 4-5

[0053] The difference from Example 1 is that the mass ratios of adipic acid-based epoxy resin to bisphenol A epoxy resin, diethylenetriamine to polyamide curing agent 650 are different, as shown in Table 2.

[0054] Table 2 Mass ratio of some components in modified epoxy resin powder and curing agent in Examples 1, 4-5

[0055]

[0056]

[0057] Example 6

[0058] The difference from Example 1 is that the modified epoxy resin only includes 100 g of bisphenol A epoxy resin and 15 g of adipic acid-based epoxy resin.

[0059] Example 7

[0060] The difference from Example 1 is that the modified epoxy resin only includes 100g of bisphenol A epoxy resin, 15g of adipic acid-based epoxy resin and 12g of hydroxypropyl quaternary ammonium salt.

[0061] Embodiment 8-9

[0062] The difference from Example 1 is that the added amounts of the various components of the modified epoxy resin are different, as shown in Table 3.

[0063] Table 3 Addition amount of each component of modified epoxy resin powder in Example 1 and Examples 8-9 / g

[0064] Example 1 Example 8 Example 9 Bisphenol A epoxy resin 100 100 100 Adipic acid based epoxy resin 15 15 15 Hydroxypropyl quaternary ammonium salt 12 14 10 Toluene-3,5-diisocyanate 17 14 20 N,N-Dimethylformamide 25 30 20 Dibutyltin dilaurate 2 1 3

[0065] Comparative Example

[0066] Comparative Example 1

[0067] The difference from Example 1 is that the modified epoxy resin powder is replaced by the same amount of bisphenol A epoxy resin, and no nano wear-resistant particles are added.

[0068] Comparative Example 2

[0069] The difference from Example 1 is that the modified epoxy resin powder is replaced with the same added amount of bisphenol A epoxy resin.

[0070] Comparative Example 3

[0071] The difference from Example 1 is that no nano wear-resistant particles are added.

[0072] Performance testing

[0073] Detection Methods

[0074] 1. Low temperature wear resistance test

[0075] Three samples were taken out from Examples 1-5 and Comparative Examples 1-3, respectively, and then smeared into a 1 mm thick sheet and cured. All samples were then placed at -20°C for 24 h, and the initial mass of the samples was immediately measured, recorded as M0. The wear resistance test was then carried out using an MM-200 wear tester, using dry grinding and sliding friction, a load of 5 kg, a rotation speed of 200 r / min, a test time of 1 h, and a test temperature of 0°C. The samples were finally weighed and recorded as M1. The low-temperature weight loss was calculated, and the low-temperature weight loss = M0-M1. The average value was taken. The test data are shown in Table 4.

[0076] Table 4 Low temperature wear resistance test table of Examples 1-5 and Comparative Examples 1-3 / g

[0077] Low temperature weight loss / mg Low temperature weight loss / mg Example 1 3.2 Example 5 4.3 Example 2 5.5 Comparative Example 1 14.9 Example 3 5.8 Comparative Example 2 8.6 Example 4 4.1 Comparative Example 3 10.1

[0078] 2. Antibacterial performance test

[0079] Three samples were taken from Example 1 and Examples 6-9, respectively, and then smeared into a 1 mm thick sheet and cured. The samples were then subjected to a simulated rain scouring operation for 1 hour, and then the antibacterial properties of the above samples were tested with reference to GB / T 21866-2008 "Determination of antibacterial properties and antibacterial effects of antibacterial coatings (paint films)", and the antibacterial rate was obtained and the average value was taken. The test data are shown in Table 5.

[0080] Table 5 Antibacterial performance test table of Example 1 and Examples 6-9

[0081] Antibacterial rate / % Antibacterial rate / % Example 1 98.7 Example 8 98.4 Example 6 60.5 Example 9 98.1 Example 7 92.4

[0082] Referring to Example 1 and Comparative Examples 1-3 and in combination with Table 4, it can be seen that relative to Example 1, the low-temperature weight loss of Comparative Examples 1-3 is significantly increased, but relative to Comparative Example 1, the low-temperature weight loss of Comparative Examples 2-3 is relatively low, which shows that the addition of modified epoxy resin powder and nano wear-resistant particles can effectively improve the low-temperature wear resistance of pipeline powder coating.

[0083] At the same time, compared with the use of modified epoxy resin powder or nano wear-resistant particles alone, when the modified epoxy resin powder is used in combination with the nano wear-resistant particles, the prepared pipeline powder coating will have better low-temperature wear resistance.

[0084] The reason is that epoxy resin is easy to wear because it is brittle and microcracks can easily expand under external forces, leading to local cracking. Molybdenum disulfide has a layered structure, and its layers are connected by weak van der Waals forces, which makes it easy for the layers to slide relative to each other during friction, helping to form a transfer film, thereby significantly narrowing the wear marks, greatly improving the delamination and peeling phenomena, and thus improving the wear resistance of the epoxy resin coating.

[0085] Copper sulfide is a hard particle that can improve the bearing capacity of the epoxy coating and play a pinning role on the network structure of the epoxy coating, thereby effectively dispersing the stress concentration caused by the friction process, inhibiting the further expansion of cracks, and thereby improving the wear resistance of the epoxy resin coating.

[0086] Compared with adding molybdenum disulfide or copper sulfide alone, adding molybdenum disulfide / copper sulfide nanohybrid materials can simultaneously obtain the transfer film function of molybdenum disulfide and the bearing capacity function of copper sulfide, thereby achieving a synergistic promotion effect and further improving the wear resistance of the epoxy resin coating.

[0087] The mechanism of low-temperature embrittlement of epoxy coatings is that the internal molecular velocity of epoxy coatings decreases at low temperatures, thus showing a high brittle characteristic. Adipic acid-based epoxy resins contain flexible chains, which improve the toughness of the entire pipeline powder system. At the same time, adipic acid-based epoxy resins also increase the freedom of macromolecular chains in the three-dimensional network of the entire pipeline powder, thereby accelerating the movement between molecules. When the pipeline powder system is impacted, a certain degree of deformation occurs, thereby absorbing the impact energy and inhibiting the further expansion of cracks. After being combined with nano-wear-resistant particles, the two will improve the low-temperature wear resistance from the two aspects of freedom and stress transfer, thereby effectively improving the low-temperature wear resistance of pipeline powder coatings.

[0088] Referring to Examples 1-3 and in combination with Table 4, it can be seen that, relative to Example 1, the low-temperature weight loss of Examples 2-3 is significantly improved, which indicates that when the components of the wear-resistant pipeline powder are added in the amounts of Example 1, the prepared pipeline powder coating will have better low-temperature wear resistance.

[0089] With reference to Example 1 and Examples 4-5 and in combination with Table 4, it can be seen that, relative to Example 1, the low-temperature weight loss of Examples 4-5 is significantly improved, which indicates that when the mass ratio of adipic acid-based epoxy resin to bisphenol A-type epoxy resin and diethylenetriamine to polyamide curing agent 650 is the same as that of Example 1, the prepared pipeline powder coating will have better low-temperature wear resistance.

[0090] Referring to Example 1 and Examples 6-7 and in combination with Table 5, it can be seen that the antibacterial rate of Example 7 is significantly improved compared with that of Example 6, which indicates that the addition of hydroxypropyl quaternary ammonium salt can effectively improve the antibacterial properties of the pipeline powder coating.

[0091] The reason is that hydroxypropyl quaternary ammonium salts can destroy the cell membranes of microorganisms, interfere with the charge balance and metabolic processes inside microbial cells, cause denaturation and inactivation of microbial proteins, and can also cause damage to microbial nucleic acids. Therefore, quaternary ammonium salts are a high-quality antibacterial material.

[0092] Compared with Example 7, the antibacterial rate of Example 1 is further improved, which shows that the modified epoxy resin powder system of Example 1 can make the pipeline powder have better antibacterial properties. The reason is that hydroxypropyl quaternary ammonium salt is very soluble in water. Therefore, when encountering rainy weather, hydroxypropyl quaternary ammonium salt is easy to precipitate, thereby affecting the antibacterial properties of the pipeline powder coating.

[0093] During the curing process of the adipic acid-based epoxy resin, the epoxy group will open the ring to form a hydroxyl group. Since the curing process is in a heated state, under the catalysis of dibutyltin dilaurate, the two isocyanate groups of toluene-3,5-diisocyanate will react with the hydroxyl group formed after the opening of the adipic acid-based epoxy resin and the hydroxyl group on the hydroxypropyl quaternary ammonium salt, respectively, thereby fixing the hydroxypropylene quaternary ammonium salt to the long chain of the pipeline powder system, effectively reducing the possibility of precipitation or deviation of the hydroxypropyl quaternary ammonium salt, and further improving the antibacterial properties of the hydroxypropylene quaternary ammonium salt.

[0094] Referring to Example 1 and Examples 8-9 and in combination with Table 5, it can be seen that the antibacterial properties of Examples 8-9 are slightly reduced compared with Example 1. This shows that when the components of the modified epoxy resin powder are added in the amounts of Example 1, the prepared pipeline powder will have better antibacterial properties.

[0095] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A wear-resistant pipeline powder, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of polyurethane powder, 40-50 parts of modified epoxy resin powder, 8-14 parts of curing agent, 15-25 parts of nano wear-resistant particles and 4-6 parts of auxiliary agent; The modified epoxy resin includes adipic acid-based epoxy resin and bisphenol A-type epoxy resin, the curing agent is obtained by mixing diethylenetriamine and polyamide curing agent 650, and the wear-resistant particles are molybdenum disulfide / copper sulfide nano-hybrid materials; The molybdenum disulfide / copper sulfide nano-hybrid material comprises the following raw materials: 0.2-0.3g of copper nitrate trihydrate, 0.05-0.15g of hexadecyltrimethylammonium bromide, 0.7-0.9g of thiourea and 0.3-0.5g of ammonium molybdate tetrahydrate; The preparation method of the molybdenum disulfide / copper sulfide nano-hybrid material comprises the following steps: S1. Add 0.25 g of copper nitrate trihydrate to 80 ml of deionized water and stir until completely dissolved, then add 0.1 g of hexadecyltrimethylammonium bromide and continue stirring until dissolved, then add 0.15 g of thiourea and continue stirring for 1 h, finally transfer to a 100 ml polytetrafluoroethylene reactor, react at 150 ° C for 12 h, and finally filter, wash and dry to obtain copper sulfide powder; S2, 0.18g of ammonium molybdate tetrahydrate and 0.3g of thiourea were added to 30ml of deionized water and mixed and stirred for 1.5h, then transferred to a 50ml polytetrafluoroethylene reactor, reacted at 210°C for 24h, and finally filtered, washed and dried to obtain molybdenum disulfide powder; S3, add 0.18g of ammonium molybdate tetrahydrate and 0.3g of thiourea to 80ml of deionized water, mix and stir for 1.5h, then add 0.05g of copper sulfide powder of S1, continue stirring for 2h and ultrasonicate for 30min, then transfer to a 100ml polytetrafluoroethylene reactor, react at 210°C for 24h, finally filter, wash and dry to obtain molybdenum disulfide / copper sulfide nanohybrid material.

2. The wear-resistant pipeline powder according to claim 1, characterized in that: The mass ratio of the adipic acid-based epoxy resin to the bisphenol A-based epoxy resin is (1-2):10; the mass ratio of the diethylenetriamine to the polyamide curing agent 650 is (1-2):

2.

3. The wear-resistant pipeline powder according to claim 1, characterized in that: The adipic acid-based epoxy resin comprises the following raw materials: 0.05-0.15 mol of adipic acid, 1.0-1.4 mol of epichlorohydrin, 0.5-1.5 mmol of benzyltriethylammonium chloride and 6-10 g of sodium hydroxide.

4. The wear-resistant pipeline powder according to claim 3, characterized in that: The preparation method of the adipic acid-based epoxy resin is as follows: first, adipic acid, epichlorohydrin and benzyltriethylammonium chloride are mixed, then reacted in a 95° C. water bath for 2 hours, then sodium hydroxide is added in portions, 1 g each time, with an interval of 15 minutes, and then reacted for 3-4 hours, and finally filtered while hot, and subjected to rotary evaporation at 125° C. to obtain the adipic acid-based epoxy resin.

5. The wear-resistant pipeline powder according to claim 2, characterized in that: The modified epoxy resin comprises the following raw materials in parts by mass: 100 parts of bisphenol A epoxy resin, 10-20 parts of adipic acid epoxy resin, 10-14 parts of hydroxypropyl quaternary ammonium salt, 14-20 parts of toluene-3,5-diisocyanate, 20-30 parts of N,N-dimethylformamide and 1-3 parts of dibutyltin dilaurate.

6. A method for preparing the wear-resistant pipeline powder according to any one of claims 1 to 5, characterized in that: The steps are as follows: polyurethane powder and modified epoxy resin powder are mixed, and then a curing agent, nano wear-resistant particles and additives are added in sequence, mixed and stirred at a stirring speed of 800-1000r / min for 10 minutes, and finally melt-extruded by a twin-screw, the melting section temperature is 180-200°C, the head extrusion temperature is 200-210°C, and finally the tablets are air-cooled, ground and sieved, the products are inspected, and the finished products are packaged and stored to obtain wear-resistant pipeline powder.

Citation Information

Patent Citations

  • Preparation method of flower-shaped molybdenum disulfide microspheres

    CN104393294A

  • Antibacterial mould-proof waterborne quaternary ammonium salt / polyurethane finishing material

    CN105694703A

  • Antibacterial wear-resistant powder paint for pipelines and preparation method of paint

    CN106497375A

  • Modified epoxy phenolic resin coating and preparation method thereof

    CN110256935A

  • Preparation method of copper sulfide electrode material and application of copper sulfide electrode material in extraction of copper from sewage

    CN114349133A